Predictors of long-term survival of hemodialysis patients in Hamadan province, west of Iran - Salman Khazaei; Mehdi Yaseri; Vida Sheikh; Mohammad Ali Mansournia (Society of Diabetic Nephropathy Prevention, 2017)
Background: Hemodialysis (HD) represents the main way of renal replacement therapy (RRT) for end-stage renal disease (ESRD) patients in Iran. Few studies have investigated the survival of HD patients in Iran. Objectives: This study conducted to reach better understanding predictors of survival for HD patients. Patients and Methods: This is a retrospective cohort study conducted in 1142 HD patients in Hamadan province during 11 years from 2007 to 2017. The checklist used to gather information was comprised of patient's demographic and clinical information. The analysis was carried out using Laplace regression and Cox regression model. Results: The most prevalent causes of ESRD were reported to be high blood pressure (BP) (28.9%) and diabetes (24.34%). The probability of survival at the end of 1st, 5th, and 10th year was 0.81, 0.4 and 0.13, respectively. Results of multivariate Cox regression showed that being rural dweller, low albumin, ferritin and hemoglobin level and having positive CRP at diagnosis have a negative significant impact on survival of HD patients (P < 0.05). Conclusions: Being rural dweller, low albumin and hemoglobin level and having positive CRP at diagnosis amongst other factors were possible factors affecting the survival of HD patients in this study. Considering the low survival probability of these patients, efforts should be made to real-time diagnosis of the cause of renal diseases.